Psychological well-being and academic self-efficacy in students at a pre-university center in Lima - Chumbimuni-Aguirre , Felix (2023)
This cross-sectional and correlational research analyzes the relationship between psychological well-being and academic self-efficacy in students over eighteen from a pre-university center in Lima. The 200 participants were selected by non-probabilistic sampling. The evaluation instruments have been the Psychological Well-Being Scale (BIEPS-A) and the Perceived Self-efficacy Scale in Academic Situations (EAPESA), whose reliability/accuracy and validation evidence based on the internal structure present adequate values. The results indicated that the correlation between psychological well-being and academic self-efficacy is positive (r = .59) and between the dimensions of the first variable and the second. In addition, analysis reveals a significant difference (p < .05) in psychological well-being, its acceptance[1]control and autonomy dimensions, and academic self-efficacy according to gender. The research results show an association between psychological well-being and academic self-efficacy of the pre-university students participating in this research.